REVIEW ON VENDOR AUDIT MANAGEMENT - Gaikwad, Priyanka Hiraman; Jadhav, Anil G.; Pathan, Vasim T.; Gujarati, Nayan A. (Asian Journal of Pharmaceutical Research and Development, 2018)
Vendor Relationship Management (SRM), is systematic planning and managing of all interactions with suppliers to maximize its value. Its application varies from construction industries to healthcare system and investment banks to industries. Several buyer-supplier relationship models, as well as supplier selection and evaluation strategies, have been documented by many researchers. The vendor management system is for supporting the good quality of material, delivery on time, good service and cooperation, reasonable price, improve the strong and close relationship, etc. The Vendor Management System (VMS) is the one most important factor of success. The vendor is the partnership that concerned to manufacturer not only the quality but also other business issues.